Implikatur Tuturan Guru dalam Pembelajaran di Sekolah Menengah Atas: Suatu Kajian Pragmatik - Anggik Budi Prasetiyo; Sukarno Sukarno; Bambang Wibisono (Jurnal Pendidikan Bahasa dan Sastra, 2022)
Learning is a process of delivering knowledge to students. Teachers as learning facilitators can use utterances that contain implicatures in them. The purpose of this study was to find and describe the form, function, and benefits of using implicatures in the teacher's utterances during the learning process. In addition, this study intends to interpret the responses of students to the teachers’ utterances that contain implicatures in it. The research data is in the form of words in the teacher's speech which are indicated to contain implicatures. The data was obtained from the transcription of recorded speeches by the teacher of Indonesian History and Indonesian Language class XII majoring in Science and Social Sciences at SMA Negeri Arjasa, Jember. The data that has been collected was analyzed using a pragmatic approach that empowers the theory of speech mode, the communicative function of speech acts, and the benefits of implicatures. The results of this study indicate that 1) there are three forms of implicature found, namely imperative, interrogative, and declarative forms, 2) several functions of implicature were found, namely the function of asking or ordering, threatening, advising, insinuating, and reprimanding), 3) there are four benefits of using implicatures, namely smoothing speech, training sensitivity, creating the impression of humor, and motivating students, 4) In addition, it can be said that students understand the teacher's speech that contains implicatures.